PROSPECTS OF SHALE GAS PRODUCTION IN THE RUSSIAN FEDERATION IN TERMS OF TECHNOLOGICAL DEVELOPMENT - A. Makovetsky; S. Kiseleva (Вестник университета)
The article addresses the question about the prospects of shale gas development in the Russian Federation. This article describes the main aspects of shale gas production, analyzes its features and ecological and economic risks. Proposed a mathematical model of a choice of variants of development of deposits of shale gas.